Climate-tectonic imprints on the Late Quaternary Ravi River Valley Terraces of the Chamba region in the NW Himalaya. (January 2022) - Joshi, M.; Thakur, V.C.; Suresh, N.; Sundriyal, Y.P.
Graphical abstract: Highlights: The present manuscript provides pristine OSL ages of the Ravi River Valley terraces, a tributary of the Indus River. Aggradation events were mainly induced by climate, whereas the incisions phases were governed by both tectonic and climate. Synchronous incision phases in Hinterland (Ravi River) and Indus plain suggest akin Late Quaternary climatic conditions. Unlike Ganga River system, Ravi River system does not show any time lag for incision between the hinterland and the plain. The first report on reactivation age (46 ka) of the MBT and the Chamba Thrust in NW Himalaya. Abstract: An attempt has been made to reconstruct the landform evolution in monsoon-dominated the Ravi River Valley (a major tributary of the Indus River), Chamba Nappe, Lesser Himalaya based on detailed field mapping, supported by the Optically Stimulated Luminescence (OSL) dates. In the upper Ravi River Valley sediments are generated by glaciation-paraglaciation processes and accumulated in terraces and alluvial fan deposits in lower reaches north of the Main Central Thrust during deglaciation and periods of intensified monsoonal phases. Field study and OSL dating demonstrate aggradation of river terraces and debris-flow terraces occurred in two major phases: 73–46 ka and 39–23 ka and at least six minor phases between <23 ka and 7 ka. The incision was initiated shortly after 7 ka and ascribed to the decrease in overall monsoon intensity and simultaneous reduction in sediment flux. The first phase (73–46 ka) of aggradation was regional and occurred in a pre-existing river valley, whereas the later phases (39 ka onward) occurred as cut-and-fill and degraded terraces. The incision of the first major phase (220 m thick) accelerated between ∼46 ka and 39 ka due to reactivation of the Chamba Thrust and the Main Boundary Thrust (MBT). The study suggests that the fluvial dynamics and aggradation phases in the Ravi River Valley were regulated by monsoon variability, whereas both tectonic activity and climatic variables governed the incision of these deposits. The contemporaneous aggradation and incision in the hinterland and the Indo-Gangetic plains suggest that the Late Quaternary climate variability was the main factor in the evolution of fluvial landforms.